EXERCISE PATTERNS IN ONLINE SOCIAL MEDIA AND THE ABILITY TO EXERCISE SELF-EXERTION OF THE ELDERLY - Phuworakij, Monchai; Chalermsuk, Thanunchai; Tabsombat, Preecha (Journal of Liberal Arts and Management Science Kasetsart University, 2022)
The objectives of this research were to study exercise patterns of the elderly through online social media and the influence of exercise patterns through online media on the ability to exercise self-exertion of the elderly. The sample population consisted of 378 elderly people in school for the elderly in Muang District, Kalasin Province, by convenient random sampling. Data were collected using survey questionnaires and statistically analyzed using percentage, mean, standard deviation and the hypothesis were tested using a multiple regression analysis method. The research results revealed that the 60-64-year elderly students’ behavior in using online media for health strengthen was at a high level, the most used application was LINE. The most popular exercise patterns of the elderly through online social media on was exercise used to improve body balance, followed by exercise to improve muscle flexibility, exercise to improve muscle strength and reduced bone mass loss, and improve stability of cardiovascular system, descending sequences. In the case of non-congenital disease elderly would choose exercise to improve muscle strength and reduce bone mass loss most. As congenital disease elderly would exercise to improve body balance. Moreover, the research revealed that exercise patterns of the elderly through online social media in relation to the ability to exercise self-exertion of the elderly in a positive direction with a significance level of 0.05.